Distributed loads in an elastic solid with generalized thermodiffusion - Choudhary, S.; Deswal, S. (Archives of Mechanics, 2008)
The linear theory of generalized thermoelastic diffusion with one relaxation time is employed to study the interactions in a homogeneous, isotropic elastic solid, when a distributed instantaneous source is acting on the free surface of the body. The eigenvalue approach is adopted for the solution of a two-dimensional problem. The Laplace–Fourier transform technique is used. The expansions of the stresses, displacement components, temperature, concentration and chemical potential are obtained analytically. Numerical results are given and illustrated graphically, employing numerical methods for the inversion for transforms. Comparisons are made with the results predicted by the theory of generalized thermoelasticity and elasticity.